1985
DOI: 10.1126/science.2990050
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin-Stimulated Release of Atriopeptin: Endocrine Antagonists in Fluid Homeostasis

Abstract: Administration of pharmacological doses of arginine-vasopressin, related peptides, and other pressor agents induced a profound release of atriopeptin immunoreactivity into the circulation. The stimulated release of atriopeptin apparently was related to increased arterial blood pressure. Neither the nonpressor vasopressin analog 1-deamino-D-Arg8-vasopressin nor arginine-vasopressin in the presence of a specific pressor antagonist caused atriopeptin to be released into the circulation. Urine output was correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
124
7
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(139 citation statements)
references
References 22 publications
7
124
7
1
Order By: Relevance
“…It has been shown that ANP secretion increases in response to vasopressin analogs and pressor agents. 33 High activity in the sympathetic nervous system decreases RBF by alpha-1-adrenergic receptors and increases sodium reabsorption and renin secretion by beta-1-adrenergic receptors in the juxtaglomerular cells. 34,35 The decrease in norepinephrine therefore contributes to the increased perfusion and increased sodium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ANP secretion increases in response to vasopressin analogs and pressor agents. 33 High activity in the sympathetic nervous system decreases RBF by alpha-1-adrenergic receptors and increases sodium reabsorption and renin secretion by beta-1-adrenergic receptors in the juxtaglomerular cells. 34,35 The decrease in norepinephrine therefore contributes to the increased perfusion and increased sodium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…A direct role of the adenohypophysis has not been clearly demonstrated and there is evidence that our surgical procedure to induce diabetes insipidus spares the adenohypophysis (see methods of Baisset & Montastruc, 1957). On the contrary, vasopressin has been shown to stimulate atrial natriuretic factor release directly or secondarily to its effect on blood volume (Manning et al, 1985;Ogawa et al, 1986). Therefore, in our control animals, at least three different factors could explain the rise in atrial natriuretic factor plasma levels: the rises in blood pressure, noradrenaline and vasopressin plasma levels.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about other factors that may influence ANP release. Adrenaline, noradrenaline, vasopressin and other agents have been shown to increase the release of ANP into the circulation both in man and experimental animals, probably via their pressor effects (Manning et al, 1985;Uehlinger et al, 1986;Ruskoaho et al, 1987;Sanfield et al, 1987). In addition, clonidine, an a2-agonist, has been shown to increase plasma levels of ANP in conscious rats (Baranowska et al, 1987a,b,c).…”
Section: Introductionmentioning
confidence: 99%